Pieśni bożonarodzeniowe w luterańskim kancjonale toruńskim - Kamper-Warejko, Joanna (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2019)
The outline addresses the set of songs included in one of the editions of the Toruń cantional by Petrus Artomius (1601). The small extract of the text provided the opportunity to grasp the range and nature of the changes taking places in the Old Polish language when the Polish culture was affected by the Reformation. For this reason, the author attempted to indicate the origin of the works and to trace the edition modifications introduced in the text with particular emphasis on linguistic alterations. In the cantional there appear texts rooted in the Polish Catholic tradition of religious songs (e.g. XVII, XX, XXI, XXVI, XXVII), translations of Protestant carols of Martin Luther known from earlier songbooks (e.g. XXX, XXXII, XXXVI); however, they are often new, modified versions of the songs. In comparison with the first edition of the cantional, the discussed edition was somewhat reorganized, which may be observed in the editor’s attempt to modernize the language of the songs. On the basis of the presented description of philological- stylistic nature one may conclude that the language of the old Protestant community of Toruń did not differ significantly from the Old Polish language of the time. On the one hand, the texts included in the cantional refer to medieval songs stylistically and linguistically. On the other hand, they illustrate the popularity and universality of Polish songs used in religious practices of Protestants, not only Lutherans.